Proceso de inducción y el desempeño laboral en la Municipalidad Provincial de Requena 2021 - Valles Trigoso, Lucerito del Carmen (2023)
The thesis focused on exploring the relationship between the induction process and work performance in the Provincial Municipality of Requena, Loreto, during 2021. A methodology applied with a non-experimental design was used, evaluating 290 employees, of which 94 were selected as a sample and the question form was applied. The findings showed that the induction process is rated as regular (26%). On the other hand, the work performance of employees is rated as medium (26%). The analysis revealed a significant correlation between the variables with a coefficient and a sig. (r=0.751; p=0.000); In the same way, the quality of service shows a coefficient and sig. of (r = 0.750; p = 0.000); productivity (r=0.657; p= 0.000); for decision-making (r=0.539; p= 0.000); and for knowledge a (r = 0.738; p = 0.000) both dimensions are significantly related to the induction process.